Prior to the issue of implementation of the principles of land law - Санніков, Д. В. (Theory and practice of jurisprudence, 2016)
Problem setting. One of the main institutions of land rights, without a doubt, you should call the Institute of ownership. Domestic legislation is the implementation of land ownership as a set of powers considering the entity on the ownership, use and disposal of land. Out of these powers is particularly important use it. This is due primarily to the fact that the use of a removal of mineral properties directly from the land. That is, the implementation of the said powers may speak not only of ownership as a set of objective and subjective features, but also consider land as a specific resource. When talking specifically about the actual implementation of land use rights, the observance of public interest, which is to save the state of the area, the environment, ecosystems, etc., occupies an equal, if not a priority, a place in the system of interest with the private. Recent research and publications analysis. At different times, the problems of implementing the principles of land law to disclose how modern Ukrainian scientists and lawyers of other countries and times, including A. Getman, G. Bashmakov, I. Ikonytska, M. Krasnov, P. Kulinich, A. Miroshnichenko, N. Titova, S. Shemshuchenko, M. Shulha and many other scientists. Paper objective. Тhe separation criterion value principles of land law, public policy analysis in the field of purposeful and rational land use and development trends of the state’s influence on social relations in order to create lawful behavior of land relations Paper main body. Тask of the state is the statutory principles of land law. In turn, the rights of owners and users of land considered to implement the removal of properties from the land so that in addition to satisfying their own interests, and there was also a strict observance of the laws of the land. However, not only the principles of statutory land law refers to national goals and qualitative monitoring their implementation. Again, given the provisions of the Constitution of Ukraine, which establishes a special significance in the system of national land values may be argued that the quality of this control should be maximum, since it deals with the main national wealth. Unfortunately, the existing system is currently monitoring the use and protection of land, perfect. This is perhaps also due to a large number of land offenses related to incompliance legislation ensuring the proper, efficient and effective use of land in Ukraine. Difficulties in controlling owners and users of land sufficient focus on this inappropriate. The main thing is, what should be emphasized is the inability of the state to ensure the proper use of all land. Thus, the state appears as a goal not only to exercise control over land use and protection, but also to ensure the proper use of land. Provision is, first and foremost, a normative character. And in this case we talk about failure that purpose, that is, the lack of regulatory consolidation responsibilities of owners and users of land, is not correct. The list of responsibilities which make land targeted, efficient and effective, available and one that meets the needs of today. But this raises the question of execution of these duties. Conclusions of the research. Еnsure compliance with state legislation aimed at implementing the principles of land law in the use of land by the respective subject is essential. Specifying the composition of such principles, narrowing their list to the principles of trust, rational, efficient use of land, priority requirements of environmental safety, economic pluralism, it should be noted that it is these principles is not given any advantage in the system of land law, this prioritization is impossible. The following specification is caused primarily by the fact that in this study are considered from principles whose implementation occurs when the use of land. But to reduce the importance of practical implementation of the aforementioned principles and should not be, because it is designed to provide a wide range of interests. In addition, as has been proven, these interests are significant not only for the state but for the whole of its population.